2007
DOI: 10.4028/www.scientific.net/msf.561-565.333
|View full text |Cite
|
Sign up to set email alerts
|

Solute Content and the Tensile Behavior of High Pressure Die Cast Mg-Al Alloys

Abstract: Binary Mg-Al alloys with varying content of aluminium from 0.5 to 12mass% have been studied. The proof stress increase in two steps whereas the ductility exhibits two correlated stepwise drops, as the aluminium content increases. The first increase in strength, and attendant drop in ductility, is observed between 4 and 5 mass% Al. The second stepwise change is observed between 10 and 12 mass% Al. These effects are connected with well defined changes in the microstructure: at 4 mass% a dispersion of β-phase int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In the current study a detailed microstructural characterization is carried out on a series of hpdc Mg-Al binary alloys to understand the role of solute content on the development of the intermetallic structure. This work builds upon our earlier studies on these alloy systems [6][7][8].…”
Section: Introductionmentioning
confidence: 84%
“…In the current study a detailed microstructural characterization is carried out on a series of hpdc Mg-Al binary alloys to understand the role of solute content on the development of the intermetallic structure. This work builds upon our earlier studies on these alloy systems [6][7][8].…”
Section: Introductionmentioning
confidence: 84%
“…It is reported that the improvement of 0.2% proof stress and tensile strength by dispersion strengthening by beta Mg 17 Al 12 phase, castability and corrosion resistance. 1,2) Solid solubility of aluminum in magnesium decreases suddenly when temperatures fall below the eutectic point. It is well-known that magnesium alloy containing aluminum more than 6 mass% has remarkable age hardability.…”
Section: Introductionmentioning
confidence: 99%